OSeac: An Online Survival Analysis Tool for Esophageal Adenocarcinoma - Wang, Qiang; Yan, Zhongyi; Ge, Linna; Li, Ning; Yang, Mengsi; Sun, Xiaoxiao; Xie, Longxiang; Zhang, Guosen; Zhu, Wan; Wang, Yunlong; Li, Yongqiang; Li, Xianzhe; et al. (Frontiers in Oncology, 2020)
Esophageal Adenocarcinoma (EAC) is one of the most common cancers in the world. However, molecular prognostic systems are still lacking for EAC. Hence, we developed an Online consensus Survival analysis web server for Esophageal Adenocarcinoma (OSeac), to centralize published gene expression data and clinical followup data of EAC patients from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). OSeac includes 198 EAC cases with gene expression profiling and relevant clinical long-term follow-up data, and employs the Kaplan Meier survival plot with hazard ratio (HR) and log rank test to estimate the prognostic potency of genes of interests for EAC patients. Moreover, we have determined the reliability of OSeac by using previously reported prognostic biomarkers such as DKK3, CTO1 and TXNIP. OSeac is free and publicly accessible at http://bioinfo.henu.edu.cn/EAC/EACList.jsp.